PEMIKIRAN FADHIL AL-SAMARRA’I TENTANG HADZF DALAM AL-QUR’AN DAN IMPLIKASINYA BAGI TAFSIR LINGUISTIK - Husnul Muawiyah Arif; Andi Nur Fadillah; Andi Abdul Hamzah; Andi Baso Pallawagau (STKIP Subang, 2026)
This article examines the thought of Fadhil Shalih al-Samarra’i, a contemporary scholar of Arabic linguistics and Qur’anic linguistic interpretation (at-ta‘bir alQur’ani), regarding the phenomenon of hadhf (ellipsis) in the Qur’an. The study addresses the limited systematic discussion of al-Samarra’i’s concept of hadhf by analyzing his understanding of ellipsis not merely as a grammatical feature of Arabic syntax and rhetoric, but as a means of revealing the precision and rhetorical excellence of Qur’anic expression. This research aims to analyze al-Samarra’i’s concept of hadhf and to identify its methodological implications for linguistic Qur’anic exegesis. A qualitative descriptive-analytical method with a library research approach was employed through an examination of al-Samarra’i’s major works, supported by classical Arabic rhetorical literature and contemporary studies on linguistic exegesis. The findings reveal that al-Samarra’i considers hadhf an essential aspect of the Qur’an’s rhetorical beauty (bayani), whose interpretation must be based on textual context (siyaq), rhetorical coherence, and communicative purpose rather than on speculative interpretation. Furthermore, this study systematizes three methodological principles underlying al-Samarra’i’s approach, namely contextuality, rhetorical coherence, and the rejection of forced interpretation. These principles contribute to the development of linguistic Qur’anic exegesis by integrating Arabic grammar, rhetoric, and contextual analysis in interpreting omitted elements of the Qur’anic text.